Evaluate Swine Wastewater Digestate for Nutrient Recovery - Thi To Uyen, Tran; Trong Tin, Nguyen; Thi Minh Hang, Tran; Quoc Dung, Nguyen; Manh Khai, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Swine wastewater is one of the environmental challenges due to the high flow rate and the high concentrations of pollutants, especially nitrogen (N) and phosphorus (P). The quality of swine wastewater after biogas treatment was assessed at farms in Hung Yen, Hanoi, and Bac Ninh. The results indicate that certain output water indicators contained concentrations exceeding limit values in national discharge standards (QCVN 62 - 2025, column B), even though the wastewater has been treated using a biogas tank system. The wastewater remains odorous, is quite turbid, and has a pH between 7.14 and 8.81. In comparison to QCVN 62-2025, the wastewater's values for organic matter, nutrients (COD, TSS, NH 4 + , PO 4 3- ) exceed the permitted standard levels: COD (639 - 5,326 mg/L); TSS (340 - 3,200 mg/L), NH 4 ⁺ (105 - 785 mg/L) and PO 4 ³⁻ (30.6 - 187.65 mg/L). The study proposes some secondary treatment techniques for post-digestion pig effluent. The principal aim is to implement a closed-loop treatment system that enables the recovery of nutrients and improves the overall quality of the released water.